THE CHOICE OF EFFECTIVE FORECASTING METHODS OF INFOCOMMUNICATION NETWORK PARAMETERS - Olha O. Leshchenko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
In the article proposed using of catastrophe theory models to predict the parameters of the control system at all stages of the life cycle, which is characterized by abrupt changes in system status.